Tree inundation period determination for mangroves rehabilitation monitoring. Issue 1 (January 2021) - Dali, H M; Mokhtar, M A M; Ghazali, N; Zainal, M Z; Zainuddin, K
Abstract: Mangroves services as coastal bioshield have been long acknowledged after the presence of mangroves has diminished a series of destructions from the extreme coastal force as a coastal barrier. However, to date, mangroves have been under threat mostly by anthropology activities. Mangroves deforestation happened at alarming rates and mangroves replanting, and rehabilitation effort yet to reach an acceptable success rate. To improve the success rate, mangroves inundation period monitoring using tacheometry method has been proposed. The approach used datum projected land elevation and mangroves tree height and overlay with annual tidal fluctuation from tide prediction tables. The output is a total inundation period for predetermined mangroves trees. Mangroves area geometry (MAG) was established at Kampung Sungai Melayu, Johor Bahru as a pilot area. Land elevation and mangroves tree height were measured using tacheometry method. Tidal fluctuations were generated based on the year 2020 Johor Bharu tidal prediction tables. From the overlay of these two datasets, five out of 40 mangroves tree in MAG area never been fully inundated but rather partly under the water surface during the high-water tide. A significant finding from the overlay is, two mangroves trees spending more than half of the year 2020 being submerged underwater and still survived. Despite the time consuming, tacheometry method for mangroves tree growth monitoring did provide a reliable and precise tree inundation period measurement.